Enhancement of syntrophic acetate oxidation pathway via single walled carbon nanotubes addition under high acetate concentration and thermophilic condition. (June 2020) - Shen, Nan; Liang, Zhu; Chen, Yun; Song, Hailiang; Wan, Junfeng
Graphical abstract: Highlights: >85% of methane was generated via SAO rather than AM pathway at 50–150 mM acetate. Almost 100% of methane was produced via SAO pathway at 200 mM acetate. SWCNT accelerated the methane production from SAO pathway. Enriched Thermacetogenium and potential DIET contributed to methane acceleration. Abstract: The effect of single walled carbon nanotubes (SWCNT) on methane production under high acetate concentration and thermophilic condition was evaluated. An isotope labeling experiment verified that >85% of methane was generated from syntrophic acetate oxidation (SAO) at 50, 100 and 150 mM acetate and almost 100% at 200 mM. SWCNT addition had little effect on the methanogenesis pathway, whereas it accelerated methane production via decreasing lag phase times and increasing maximum methane production rates. Electrochemical impedance spectroscopy (EIS) results revealed the electrical resistivity of sludge in groups of SWCNT was distinctly smaller than CK groups, indicating higher sludge conductivity was achieved. Further, the results of communities described that Coprothermobacter and Thermacetogenium played the most important role in SAO under all conditions. Meanwhile, the enriched Thermacetogenium and direct interspecies electron transfer (DIET) pathway in SAO consortia contributed to the acceleration of methane production via SWCNT addition.